The 2013 update of the OECD's database on product market regulation Policy insights for OECD and non-OECD countries - Koske, Isabell (OECD Economics Department Working Papers, 2015)
This paper investigates patterns in product market regulation across 34 OECD and 21 non-OECD countries, using an updated and revised version of the OECD's indicators of product market regulation (PMR). The analysis shows that liberalisation of product markets has further slowed over the past five years. However, even though there was little progress on average in the OECD over this period, a number of OECD countries implemented sizable reforms, often in an attempt to boost economic growth in wake of the economic crisis. On average across the OECD, countries have made particular progress in abolishing price controls or improving their design, streamlining administrative procedures for start-ups, simplifying rules and procedures or improving access to information about regulations. Room for further improvements is the largest in the areas of public ownership and the governance of state-owned enterprises as well as with respect to barriers to competition in network and services sectors